Comorbidities of Primary Headaches During Pregnancy and the Perinatal Period: An Integrative Review - Bala, Christina; Eline, Tommelein; Kararizou, Evangelia; Diamanti, Athina; Vivilaki, Victoria (British Journal of Healthcare and Medical Research, 2025)
Introduction: This article provides an overview of available information regarding Primary Headaches (PH) during pregnancy and the postpartum period with a focus on their comorbidities such as psychiatric disorders (depression, anxiety, stress, post-traumatic stress disorder), sleep disorders, abuse and potential trigger factors such as assisted reproductive techniques and smoking. Methods: A systematic search was conducted on five electronic databases, PubMed, Embase, Web of sciences, Scopus and Cochrane Library, spanning from January 1983 to August 2024, for pertinent manuscripts. The collected datasets were summarized and synthesized descriptively. Results: Nineteen manuscripts were incorporated into the analysis. Among them, half employed self-report methods to classify headaches, while 14 utilized validated questionnaires and scales to evaluate psychiatric and sleep disorders, as well as intimate partner violence. Additionally, the results of a case study and a letter to the editor were also included in the compilation. Primary Headaches are associated with psychiatric and sleep disorders, intimate partner violence and assisted reproductive techniques during perinatal period. Depression, anxiety and stress are more prevalent among pregnant individuals suffering from migraines compared to those without the condition. Discussion: Accurate diagnosis is crucial for the effective management of headaches experienced by pregnant and postpartum women. This review underscores the necessity for research studies evaluating headaches and their correlated conditions at various points around the perinatal period. The implementation of early screening protocols and crafting customized treatment strategies can greatly improve the quality of care offered to women during the perinatal period.